Microparticle detection in platelet products by three different methods. Issue 1 (25th May 2012) - Strasser, Erwin F.; Happ, Sebastian; Weiss, Dominik R.; Pfeiffer, Alexandra; Zimmermann, Robert; Eckstein, Reinhold
<x xml:space="preserve">Abstract</x> BACKGROUND: Standardization of platelet‐derived microparticle (PMP) enumeration by flow cytometry (FCM) is limited due to its intrinsic characteristics. Because of high clinical relevance of microparticle (MP) detection, standardization of MP assays is required. STUDY DESIGN AND METHODS: This prospective paired study analyzed 31 healthy blood donors (18 male, 13 female) and compared pre‐ and postdonation results of donors with results of plateletpheresis products by three different methods. PMP counts were analyzed by FCM using calibrated beads of defined diameter and annexin V‐fluorescein isothiocyanate and CD41‐phycoerythrin staining. MP activity was tested by prothrombinase assay (enzyme‐linked immunosorbent assay [ELISA]) and a procoagulant phospholipid‐dependent clotting time assay (STA‐Procoag‐PPL, Diagnostica Stago S.A.S.). RESULTS: PMP concentration was more than threefold higher in single‐platelet units (SPUs) and resulted in higher PMP yields in SPUs compared to double‐platelet units (DPUs). The ELISA and the procoagulant clotting assay also revealed a significant higher MP activity in SPUs compared to DPUs. The results of the procoagulation clotting assay correlated inversely with PMP counts obtained by FCM (r = −0.685, p < 0.001) and with the MP activity measured by ELISA (r = −0.641, p < 0.001). CONCLUSION: Three different methods for MP detection showed good correlations of results, albeit the basis for MP analysis was different. Even if FCM is considered the "gold standard" of MP detection there are still technical limitations concerning detection of small MP. The procoagulant STA‐Procoag‐PPL assay and the prothrombinase ELISA assay could be useful additional MP tests. Regarding the interpretation of quantitative results of MPs, preanalytical conditions must be optimized and standardized.